An open‐ended primary‐care group intervention for insomnia based on a self‐help book – A randomized controlled trial and 4‐year follow‐up. (11th June 2019) - Kaldo, Viktor; Bothelius, Kristoffer; Blom, Kerstin; Lindhe, Maria; Larsson, Matilda; Karimi, Kobra; Melder, Susanne; Bondestam, Viveka; Ulfsparre, Charlotte; Sternbrink, Klara; Jernelöv, Susanna
Summary: Chronic insomnia is a common and burdensome problem for patients seeking primary care. Cognitive behavioural therapy has been shown to be effective for insomnia, also when presented with co‐morbidities, but access to sleep therapists is limited. Group‐treatment and self‐administered treatment via self‐help books have both been shown to be efficacious treatment options, and the present study aimed to evaluate the effect of an open‐ended group intervention based on a self‐help book for insomnia, adapted to fit a primary‐care setting. Forty primary‐care patients with insomnia (mean age 55 years, 80% women) were randomized to the open‐ended group intervention based on a cognitive behavioural therapy for insomnia self‐help book or to a care as usual/wait‐list control condition. Results show high attendance to group sessions and high treatment satisfaction. Participants in the control group later received the self‐help book, but without the group intervention. The book‐based group treatment resulted in significantly improved insomnia severity, as well as shorter sleep‐onset latency, less wake time after sleep onset, and less use of sleep medication compared with treatment as usual. The improvements were sustained at a 4‐year follow‐up assessment. A secondary analysis found a significant advantage of the combination of the book and the open‐ended group intervention compared with when the initial control group later used only the self‐help book. An open‐ended treatment group based on a self‐help book for insomnia thus seems to be an effective and feasible intervention for chronic insomnia in primary‐care settings.